Laboratoires vivants en innovation sociale et coconstruction des connaissances dans les villes : les cas du TIESS (Montréal) et de l’OBISF (Florianópolis) - Magalhaes, Thiago; Camus, Annie; Andion, Carolina; Tello-Rozas, Sonia (Revue Organisations & territoires, 2020)
Le débat sur le rapport entre l’innovation sociale et les villes s’est élargi au cours des dernières décennies. Ce débat met en évidence l’intérêt suscité par les processus de coconstruction des savoirs dans les laboratoires vivants en innovation sociale (LVIS). Cet article a pour objectif de présenter une approche conceptuelle et analytique du traitement des LVIS, ainsi que de décrire et de mettre en perspective deux expériences de mise en oeuvre de LVIS dans les villes : l’Observatoire de l’innovation sociale de Florianópolis (OBISF) au Brésil et Territoires innovants en économie sociale et solidaire (TIESS) à Montréal au Canada. Bien qu’ils émergent dans des réalités et des contextes différents avec des méthodologies de mise en oeuvre spécifiques, qui sont présentées dans le texte, la discussion et l’analyse des deux cas apportent des pistes d’apprentissage sur les défis et les perspectives quant à la coconstruction des connaissances visant à renforcer les dynamiques d’innovation sociale à l’échelle d’une ville.
Keywords: Brésil; Canada; Co-construction; Laboratoire vivant; Living Labs; Montréal; Réservé UdeM; Urbanisme; Économie sociale; Économie solidaire

Knowledge transfer for frugal innovation: where do entrepreneurial universities stand? - Fischer, Bruno; Guerrero, Maribel; Guimón, José; Schaeffer, Paola Rücker (Journal of Knowledge Management, 2020)
Frugal innovation has gained prominence based on its potential contribution to sustainable development and the new opportunities that it offers to low-income customers. This paper aims to analyse the strategic knowledge transfer practices implemented by an entrepreneurial university for fostering frugal innovations within an emerging economy. Design/methodology/approach This study adopted a case study methodological approach. The selected case was the University of Campinas (Unicamp), one of the leading universities in Brazil in terms of research quality and technology transfer. The study built upon 14 interviews with key informants and secondary sources of data (official and public documents). Findings The findings highlight the multidimensional dynamics of frugal innovations arising from university–industry relationships. Key dimensions considered include the internal capabilities of universities to foster frugal innovations and connect them to markets, the surrounding innovation ecosystems in which the university is embedded and the overarching institutional framework. Research limitations/implications The analysis of strategic management practices for frugal innovation requires an evolutionary perspective, but the findings lacked sufficient longitudinal information for a formal evaluation. Also, as our empirical analysis is based on an in-depth case study of one university, further validation in other contexts would be necessary. Practical implications This study offers new insights regarding the effectiveness of university-business collaboration partnerships for developing frugal innovations in emerging economies. Policymakers should promote societal programs enhancing the active participation of all agents involved in the entrepreneurial and innovation ecosystem. University managers should understand the challenges and the opportunities behind the adoption of an inclusive and societal orientation. Social implications By adopting frugal innovation practices, universities can enhance their contribution of meeting the United Nations’ Sustainable Development Goals. Originality/value The literature on frugal innovation has emphasized the importance of networking between different types of firms, NGOs and governments, but the role of universities in frugal innovation remains mostly unexplored. This study addresses this gap by exploring how entrepreneurial universities participate in frugal innovations to meet societal challenges.
Keywords: Brésil; Innovation frugale; Réservé UdeM; Rôle des universités

Knowledge transfer for frugal innovation: where do entrepreneurial universities stand? - Fischer, Bruno; Guerrero, Maribel; Guimón, José; Schaeffer, Paola Rücker (Journal of Knowledge Management, 2020)
Frugal innovation has gained prominence based on its potential contribution to sustainable development and the new opportunities that it offers to low-income customers. This paper aims to analyse the strategic knowledge transfer practices implemented by an entrepreneurial university for fostering frugal innovations within an emerging economy. Design/methodology/approach This study adopted a case study methodological approach. The selected case was the University of Campinas (Unicamp), one of the leading universities in Brazil in terms of research quality and technology transfer. The study built upon 14 interviews with key informants and secondary sources of data (official and public documents). Findings The findings highlight the multidimensional dynamics of frugal innovations arising from university–industry relationships. Key dimensions considered include the internal capabilities of universities to foster frugal innovations and connect them to markets, the surrounding innovation ecosystems in which the university is embedded and the overarching institutional framework. Research limitations/implications The analysis of strategic management practices for frugal innovation requires an evolutionary perspective, but the findings lacked sufficient longitudinal information for a formal evaluation. Also, as our empirical analysis is based on an in-depth case study of one university, further validation in other contexts would be necessary. Practical implications This study offers new insights regarding the effectiveness of university-business collaboration partnerships for developing frugal innovations in emerging economies. Policymakers should promote societal programs enhancing the active participation of all agents involved in the entrepreneurial and innovation ecosystem. University managers should understand the challenges and the opportunities behind the adoption of an inclusive and societal orientation. Social implications By adopting frugal innovation practices, universities can enhance their contribution of meeting the United Nations’ Sustainable Development Goals. Originality/value The literature on frugal innovation has emphasized the importance of networking between different types of firms, NGOs and governments, but the role of universities in frugal innovation remains mostly unexplored. This study addresses this gap by exploring how entrepreneurial universities participate in frugal innovations to meet societal challenges.
Keywords: Brésil; Innovation frugale; Réservé UdeM; Rôle des universités

Laboratoires vivants en innovation sociale et coconstruction des connaissances dans les villes : les cas du TIESS (Montréal) et de l’OBISF (Florianópolis) - Magalhaes, Thiago; Camus, Annie; Andion, Carolina; Tello-Rozas, Sonia (Revue Organisations & territoires, 2020)
Le débat sur le rapport entre l’innovation sociale et les villes s’est élargi au cours des dernières décennies. Ce débat met en évidence l’intérêt suscité par les processus de coconstruction des savoirs dans les laboratoires vivants en innovation sociale (LVIS). Cet article a pour objectif de présenter une approche conceptuelle et analytique du traitement des LVIS, ainsi que de décrire et de mettre en perspective deux expériences de mise en oeuvre de LVIS dans les villes : l’Observatoire de l’innovation sociale de Florianópolis (OBISF) au Brésil et Territoires innovants en économie sociale et solidaire (TIESS) à Montréal au Canada. Bien qu’ils émergent dans des réalités et des contextes différents avec des méthodologies de mise en oeuvre spécifiques, qui sont présentées dans le texte, la discussion et l’analyse des deux cas apportent des pistes d’apprentissage sur les défis et les perspectives quant à la coconstruction des connaissances visant à renforcer les dynamiques d’innovation sociale à l’échelle d’une ville.
Keywords: Brésil; Canada; Co-construction; Laboratoire vivant; Réservé UdeM; Urbanisme; Économie sociale; Économie solidaire